A Study On The Implementation Of Word Chain Game In Teaching Vocabulary Mastery - Vivi Vidya Lestari; Darmawan Darmawan; Wahyudin Wahyudin; Mafulah Mafulah (Hasanuddin University, 2025)
This study investigates the implementation of the Word Chain Game as a strategy to enhance vocabulary mastery among students learning English as a Foreign Language (EFL). Utilizing a library research method with a qualitative descriptive approach, this research synthesizes findings from five recent studies conducted between 2018 and 2023. The results consistently indicate that the Word Chain Game is an effective tool for improving students’ vocabulary acquisition, engagement, and confidence in using new words. Teachers have applied both oral and written forms of the game, integrating it into thematic lessons to make vocabulary learning more contextual and enjoyable. Despite its advantages, some challenges remain, including time constraints, classroom management in large groups, and the need for alignment with curriculum goals. Nevertheless, the benefits—such as increased vocabulary retention, higher test scores, and reduced student anxiety—demonstrate the game’s pedagogical value. This study concludes that the Word Chain Game is a practical and engaging method for teaching vocabulary in EFL settings and recommends its inclusion in language teaching practices, with consideration given to proper adaptation and teacher training. Future research could explore integrating the game with digital tools to further enhance its effectiveness.